Digital ecosystems simulation prototype - Wu, Chen; Mao, G.; Izquierdo, A. (Curtin University of Technology, 2008)
The exhibit which features the ‘Digital Ecosystems Simulation Prototype’ formed part of the major exhibition of Curtin University of Technology 'The pursuit of knowledge: Curtin, Looking ever forward' which was opened by His Excellency, Dr Ken Michael, AC, Governor of Western Australia on 26 March 2008. The exhibition will be on display in the Wesfarmers exhibition space of the John Curtin Gallery on the University’s Bentley campus until 2012. The Digital Ecosystem display includes a lively interactive computer simulation program which allows visitors to play around and see how digital ecosystems react to different stimuli. An accompanying interpretative panel explains the research in easy to understand text. The exhibition was developed by the John Curtin Prime Ministerial Library, which is Australia's first prime ministerial library and forms part of the Library at Curtin University of Technology, in Perth, Western Australia. The exhibition explores the shared beliefs of Curtin the man and Curtin the university - noting the passionate commitment of each to education and the pursuit of knowledge. From John Curtin's own education and the initiatives of his war time government in furthering tertiary education and research, the exhibition moves to a focus on the University and showcases some of the significant, innovative and exciting research currently being undertaken at Curtin.